Impact of Depression on Patients With Hemophilia: A Retrospective Case-Control Research - Jiménez-Cebrián, Ana María; Palomo-López, Patricia; Becerro-de-Bengoa Vallejo, Ricardo; Losa-Iglesias, Marta Elena; Navarro-Flores, Emmanuel; San-Antolín, Marta; Calvo-Lobo, César; López-López, Daniel (Frontiers in Psychiatry, 2022)
Background: Haemophilia is an inherited recessive hemorrhagic disorder of the X-linked type, suffered by male sex. Adult haemophiliacs are coping with numerous diagnostics, associated comorbidities, pain and difficulty gait by arthropathy in ankles and feet. Physical pains contribute to depression in haemophiliacs. Purpose: The aim of the study was to assess the impact of depression in adults haemophiliacs patients also to compare with healthy matched-paired controls. Methods: The sample consisted of 100 participants (median age 42.50±30.00). Haemophiliacs were recluted from Spanish Haemophiliac Associations (n=50) and healthy subjects (n=50) from a Clinic Podiatry Practices (University of Malaga, Spain). Results: Results and categories of Spanish-translated version of the Beck Depression Inventory (BDI) were gathered. A clear statistically significant difference (p < 0.001) was presented at the variation of the BDI scores between both groups. Haemophiliacs presented worse results of the BDI = 7.50 ± 11.25 points compared to healthy subjects with BDI = 2.50 ± 5.00 points. The BDI categories, statistically significant differences (p = 0.004) were found to greater BDI categories in the haemophilia group compared with healthy subjects. Moderate and severe depression categories were only showed in haemophilic patients. Conclusions: Greater depression scores and ranges status was observed in haemophiliacs compared to non-haemophiliacs. Haemophiliacs are at increased risk of depressiveness.